Dokumen kontrak tambahan (tempoh lanjutan) : inspection, servicing, preventive and breakdown maintenance of fire protection installation and auxilliary equipment at Universiti Teknologi Malaysia Skudai Johor - Universiti Teknologi Malaysia; Bersia Engineering Services (M) Sdn. Bhd. (Skudai : Universiti Teknologi Malaysia, 2003)
03